Connected Lie Groupoids are Internally Connected and Integral Complete in Synthetic Differential Geometry - Burke, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We extend some fundamental definitions and constructions in the established generalisation of Lie theory involving Lie groupoids by reformulating them in terms of groupoids internal to a well-adapted model of synthetic differential geometry. In particular we define internal counterparts of the definitions of source path and source simply connected groupoid and the integration of A-paths. The main results of this paper show that if a classical Hausdorff Lie groupoid satisfies one of the classical connectedness conditions it also satisfies its internal counterpart.